Linking ringed seal foraging behaviour to environmental variability - Nykänen, Milaja; Niemi, Marja; Biard, Vincent; Carter, Matt I. D.; Pirotta, Enrico; Kunnasranta, Mervi (BioMed Central, 2025)
Background Foraging rates directly influence animals’ energetic intake and expenditure and are thus linked to body condition and the ability to survive and reproduce. Further, understanding the underlying processes driving a species’ behaviour and habitat use is important as changes in behaviour could result from changes in environmental conditions. Methods In this study, the dives of Saimaa ringed seals (Pusa hispida saimensis) were classified for the first time using hidden Markov models and telemetry data collected on individual dives, and the behavioural states of the diving seals were estimated. In addition, we used generalized additive mixed models on the foraging probability of the seals to identify environmental and temporal drivers of foraging behaviour. Results We inferred three (in winter) or four (in summer) different dive types: sleeping/resting dives, shallow inactive dives, transiting dives and foraging dives, based on differences in dive metrics logged by or derived from data from telemetry tags. Long and relatively deep sleeping/resting dives were missing entirely in the winter, compensated by an increased proportion of time used for haul-out. We found profound differences in the behaviour of Saimaa ringed seals during the open water season compared to the ice-covered winter, with the greatest proportion of time allocated to foraging during the summer months (36%) and the lowest proportion in the winter (21%). The seals’ foraging probability peaked in summer (July) and was highest during the daytime during both summer and winter months. Moreover, foraging probability was highest at lake depths of 7–30 m in the winter and at depths > 15 m in the summer. We also found some evidence of sex-specific foraging strategies that are adapted seasonally, with females preferring more sheltered water areas during winter. Conclusions We suggest that the foraging behaviour of Saimaa ringed seals is largely influenced by diel vertical movements and availability of fish, and that the seals optimize their energy acquisition while conserving energy, especially during the cold winter months. Further, the seals display some flexibility in foraging strategies, a feature that may help this endangered subspecies to cope with the ongoing climate change.
Keywords: ringed seal; Pusa hispida saimensis; foraging behaviour